2018
DOI: 10.25077/jka.v7i2.813
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor yang Berhubungan dengan Kejadian Stunting pada Anak Usia 24-59 Bulan di Wilayah Kerja Puskesmas Andalas Kecamatan Padang Timur Kota Padang Tahun 2018

Abstract: Stunting merupakan keadaan indeks tinggi badan menurut umur di bawah minus dua standar deviasi berdasarkan standar WHO.. Stunting merupakan manifestasi jangka panjang faktor konsumsi diet berkualitas rendah, penyakit infeksi berulang, dan lingkungan. Tujuan penelitian ini adalah mengetahui faktor-faktor yang berhubungan dengan kejadian stunting pada anak usia 24-59 bulan. Jenis penelitian ini adalah studi analitik observasional dengan desain cross-sectional. Sebanyak 74 sampel dipilih secara simple random samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
1
101

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(139 citation statements)
references
References 0 publications
4
33
1
101
Order By: Relevance
“…The insignificance of historical relations of infectious diseases with stunting incidents in this study, could be due to the influence of the duration or the length of infex disease or the status of the intake of nutrients at all times the occurrence of infectious diseases (29). Children with short periods of time pain or good intake of nutrient during illness may reduce the risk of stunting children.…”
Section: Correlation History Of Infectious Diseases With Stunting Incmentioning
confidence: 64%
“…The insignificance of historical relations of infectious diseases with stunting incidents in this study, could be due to the influence of the duration or the length of infex disease or the status of the intake of nutrients at all times the occurrence of infectious diseases (29). Children with short periods of time pain or good intake of nutrient during illness may reduce the risk of stunting children.…”
Section: Correlation History Of Infectious Diseases With Stunting Incmentioning
confidence: 64%
“…The prevalence of stunting in Indonesia ranks fourth in Asia, with a prevalence of 36.4% [2]. This prevalence is also higher than the research conducted by [13] which revealed that the stunting percentage reached 26.9 percent.…”
Section: Methodsmentioning
confidence: 99%
“…Stunting children is considered as chronic nutritional disorder caused by various factors including history of infectious diseases, health services, immunization status, exclusive breastfeeding, zinc and iron adequacy levels, maternal height <150 cm, maternal age, parent education level, mother's knowledge, family income, food availability in family, food diversity, sanitation, energy intake level, duration of infectious disease history, birth weight, birth length, and genetics. From the above factors, the most dominant factors affecting stunting in children are exclusive breastfeeding and adequate nutrition during pregnancy and after child birth 1,[3][4][5][6][7][8] .…”
Section: Risk Factormentioning
confidence: 99%